Modern Business Philosophy: the Brand as a Phenomenon of Culture - V. Golik, Nadezhda; I. Izvekov, Arkady; ., . (International Journal of Engineering and Technology, 2018)
The concept of brand as a set of information about a company, product or service, legally protected by recognizable symbols, is well known. Significantly less studied brand as a phenomenon of the art market. In this context, the goal of the research was formulated – to identify the signs of the brand, which is not just a part of the business culture, but a cultural phenomenon in general. We had to discuss a number of other aspects. First, the influence of the historical roots of culture on the formation of the brand. Secondly, the receptivity of the brand's creators to the aesthetic ideals of culture of different eras. Third, the ability to maintain ethical and high standards of culture in the development of the brand. The practical value of the research can be attributed to the possibility of applying its results in real business practice in the luxury retail management.